CONSUMER BEHAVIOR TOWARDS DEALER PURCHASING PATTERN IN MALLIGHAI MANAGRAM - DR. S. ANTONY RAJ (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Dealer is creating an essential role in the marketing because it encounters the end consumer by the purpose of exchange the goods and services in small level. the dealer is the last link between the manufacture and final consumer. in the present scenario the dealer has occupied their physical presence in the form of store and also generate the economic activities. dealer in business has emerged in easy way to meet requirement of customer demand and ensure the real time value in the from of product thereby providing an opportunities to customer to evaluate stores in a stipulated time hence dealer is not giving any material but assured the finished goods to consumer in the way of formulate the shop to express their preference under customer domain .The Research paper has revealed that area of Madurai city is called Mallighai Managram attempt to know customer attitudes towards Dealer purchasing pattern namely multi brand stores, single brand stores, e – retail, commodity accessibility under budget for buyer and so on.